Evaluation of mechanical properties and cracking resistance of shrinkage-compensating concrete reinforced by expansive agents with polypropylene fibers - Wenxiao Lu; Ji Chen; Qiang Tang; Fan Gu (Case Studies in Construction Materials)
Concrete sidewalls are crucial in construction, yet their deformation control during casting and curing due to heat dissipation is a significant challenge. This often leads to issues such as shrinkage and cracking, which can compromise the structural integrity and functionality of the sidewalls. To overcome these issues, this study aimed to investigate the feasibility of adding expansion agent (EXP) and polypropylene fiber (PPF) to concrete for shrinkage compensation and crack resistance. A series of laboratory tests, including slump, compressive strength, flexural strength, X-Ray diffraction (XRD), and scanning electron microscope (SEM) tests, were carried out to analyze the mechanical properties and cracking-resistance mechanism of EXP and PPF reinforced concrete. Furthermore, a full-scale concrete sidewall was constructed, and sensor monitoring was implemented to measure temperature, stress, and strain variations. Numerical simulation of crack developing process was also conducted. The results showed that EXP reduced the early-age concrete strength but had a negligible effect on the final strength. Both EXP and PPF enhanced the ductility of concrete. The optimal mix was identified as concrete with 9 % EXP and 0.3 % PPF, exhibiting desirable compressive and flexural strengths and adequate ductility. The sensor monitoring of the full-scale sidewall showed that the internal temperature variation could reach 40 °C during curing, indicating that EXP alleviated heat from hydration and compensated for concrete shrinkage. Both the full-scale monitoring and numerical simulation results confirmed that the combined use of EXP and PPF enhanced the ductility of concrete and prevented the generation and propagation of microcracks in the concrete sidewall.